"If You Build It…": Methodological Approaches to Detect Postrestoration Responses in Stream Fishes. Issue 8 (17th March 2022) - Polivka, Carlos M.
Abstract : Habitat restoration to recover fish populations takes place worldwide, yet studies of its efficacy are fraught with challenges. One difficulty comes from studies of fish responses that are too focused on whether abundance has increased in the restored habitat, limiting the methodology to observational data of fish density. However, many other tools are available for evaluation of restoration. I review a set of conceptually based methods that colleagues and I used to assess restoration efficacy in a model river system to show the strength of considering alternative approaches. Although it was relatively easy to determine that fish are attracted to instream restoration structures (engineered log jams), spatial and temporal variability in the results requires approaches that more closely examine the distinction between increases in density and increases in habitat capacity. Furthermore, I show that efficacy research should be augmented with consideration of behavior, the spatial scale of the post‐restoration studies, the response of life history traits (e.g., growth), and the applicability of habitat selection theory. These detailed studies often, but not always, identify benefits of restoration that go beyond simple observations of fish abundance. They are therefore methods that are worth considering by researchers involved in postrestoration fish monitoring.